جودة اتخاذ القرار وأنماط القيادة الرياضية لدى حكام كرة القدم في محافظة بابل - العوادي, جاسم جابر; الكناني, عايد كريم (Sulaimani Journal for Humanities, 2018)
The problem of research was manifested in the lack of interest in psychological aspects and practical arbitration as well as theoretical and the lack of research studies in this field And the lack of availability of mathematical sports standards that are concerned with building the quality of decisions made by the referee and the sports leadership styles , As the sports leadership styles are influenced by the personal factors of the referee's behavior during his leadership of the game and his ability to control the course of the game and to produce positive results in line with the International Arbitration Law , The study aimed to codify the decision- making standards and sports leadership styles of football referees, to identify the quality of decision-making and their sports leadership styles, and to establish the relationship between the quality of decision-making and the sports leadership styles of football referees. The researchers used the descriptive approach in survey methods, correlative relations and standard studies to suit the nature of the research problem. The sample of the rationing included (50) judgments representing the research community , The researchers used the criteria of quality decision making and mathematical leadership styles prepared by researcher (Aziz Kareem) as well as statistical tools through the statistical basket of social sciences (SPSS). The most important conclusions reached by the researchers standardize the standards of decision-making and sports leadership styles of football referees in the province Babel The researchers also found that there is no relationship between the quality of decision-making and sports leadership styles as well as the importance of the role of quality in decision-making arbitration, which is reflected on the nature of sports leadership during the refereeing of matches.